Parental perception of treatment options for mucopolysaccharidosis: a survey to bridge the gap for personalized medicine - Anna-Maria Wiesinger; Florian B. Lagler (Orphanet Journal of Rare Diseases)
Abstract Background Mucopolysaccharidosis (MPS) are a group of lysosomal storage diseases with substantial unmet medical needs—for both patients and caregivers. Approved therapies are limited, and the perception of investigative ones remains enigmatic. Method Using an innovative survey concept based on the discrete choice experiment method (DEC) with neuronopathic and non-neuronopathic patient scenarios, we aimed to evaluate how parents of children with MPS perceive different approved and innovative therapies. The questionnaire was distributed via patient organizations in Germany, Switzerland, and Austria. Results Most likely parents would choose an approach to repurposed treatments for their child (neuronopathic: 82%, 14/17 and non-neuronopathic: 94%, 16/17), followed by enzyme replacement therapy (ERT, both 88%, 15/17), hematopoietic stem cell therapy (HSCT, 70%, 12/17 and 76%, 13/17), and finally gene therapy (GT, 58%, 10/17 and 53%, 9/17). The general attitudes strongly influenced decision-making regarding treatment options. While over 80% of respondents who held a positive attitude toward ERT, HSCT, and ITTs indicated they would opt for these therapies in both neuronopathic and non-neuronopathic cases, only about half of the parents with a favorable general view of gene therapy (GT) expressed a positive perception of its likelihood as a treatment option. Furthermore, most parents found mild infections, injection site reactions (ISRs), hypertonia, and treatment-related hospitalizations acceptable and indicated patient organizations as their main source of information. Conclusions This study provides an innovative survey method, thereby offering the rationale for a quantitative risk–benefit model and the importance of patient and caregiver-centered information dissemination, especially for innovative therapies.